How do you multiply (3x + 2)(4x - 5) ?

2 Answers
Mar 5, 2018

12x^2 -7x -10

Explanation:

Multiply each term with each other

  1. (3x) xx (4x) = 12x^2
  2. (3x) xx (-5) = -15x
  3. 2 xx 4x = 8x
  4. 2 xx (-5) = -10

So

12x^2 -15x +8x -10

12x^2 -7x -10

Mar 5, 2018

12x^2-7x-10

Explanation:

To multiply polynomials, you have to multiply the terms in the left by the terms on the right so multiply 3x by 4x and -5 and do the same to 2. You should get this once you're done:
12x^2-15x+8x-10

After you multiplied the polynomials, combine the like terms
12x^2-7x-10